(untitled) (Latakia University Journal -Biological Sciences Series, 2020)
This research aimed to estimate the optimum medium for the in vitro propagation of some genotypes of Rosa damascena Mill., that have been phenotypically and molecularly describe. single-node explants were surface sterilized and cultured on Murashig and Skoog medium (MS) supplemented with various combinations of growth regulators (NAA, IBA and BA) at different concentrations.1- Shoot proliferation was best on Ms medium supplemented with (0.25mg/ l NAA + 4 mg / l BA) with 3.41 migroshoots subculture after 4 weeks of planting.2- The highest elongation ratio was on T3: (MS + 0.5mg / l NAA + 2 mg / l BA). 3- Efficient (95%) was achieved on half-strenth MS medium with (0.4 mg / l IBA). 4- The results indicated that the RD4 genotype was superior the average number of growths, while the RD1 genotype was superior the rest of the genotypes by rooting and average root length and number. Rooted plantlets were gradually acclimatised for 4 weeks and planted out under field with a survival over 80% at RD1 and 75% at other studied genotypes.